Wawasan Al-Qur’an Tentang Zakat dan Kemiskinan: Studi Ekonomi Syariah di Barru - Achmad Riady; Achmad Abubakar; Muhammad Irham (AMAL: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the effect of zakat distribution on poverty reduction in Barru Regency from the perspective of Islamic economics grounded in Qur’anic insight. Poverty remains a central issue in the region, despite the potential of zakat and the active role of zakat management institutions. A quantitative approach was employed using a simple linear regression analysis, based on secondary data from BAZNAS and BPS for the period 2020–2024. The results reveal that zakat distribution has a significant influence on reducing poverty levels, with a determination coefficient of 0.672. These findings indicate that increased zakat distribution corresponds with lower poverty rates in the area. The theoretical discussion is supported by the concept of zakat as an empowerment tool for the poor and its relevance to maqashid shariah and sustainable development goals. This study concludes that optimizing zakat distribution, particularly through productive programs, can serve as a concrete solution to localized and just poverty alleviation. Keyword: Zakat, Poverty, Islamic Economics, Qur’anic Insight